The house on hope street - Steel, Danielle (London : Corgi Books, 2001)
Liz and Jack Sutherland seem to have everything, with a happy family and a thriving business. Then Jack is shot, and Liz is left to cope all by herself. She rebuilds her life, facing the trials and tribulations, and then meets a doctor called Bill.
Keywords: Physicians -- Fiction; Domestic fiction